МОНГОЛ ХҮНИЙ БАТГА ҮҮСГЭГЧ, ЭМГЭГШҮҮЛЭГЧИЙГ ТОДОРХОЙЛСОН ДҮН - Н, Оюунбилэг; М, Энхцацрал; Б, Болортуяа; Б, Даваапүрэв; Р, Чинзориг; Ё, Анзай; Г, Номиндалай; Ж, Энхжаргал; Ж, Батхүү (Proceedings of the Mongolian Academy of Sciences, 2017)
The skin is thin layer of tissue forming the natural outer covering of the body of a person, it is protected from some infections [1]. Skin’s naturally occurring microbes are Staphylococcus, Micrococcus, Corynebacterium, Brevibacteria, Propionibacteria and Acinetobacteria [2, 3]. Acnes caused by Propionibacterium acnes (P.acnes) infection but it is commensal with other microorganisms. Sometimes P.acnes identified in normal skin. P. acnes live deep within follicles oil-bag and pores, away from the surface of the skin. Elevated production of sebum by hyperactive sebaceous glands (sebaceous hyperplasia) or blockage of the follicle can cause P. acnes to grow and multiply. Acne is chronic inflammatory disease affecting the pilosebaceous follicle [18]. Skin infections are decreasing immunity of certain parts of the body. Acne severity correlated highly with increasing stress and harmful for self-confidence [4]. The most countries had study about their acne patient’s microflora and pathogenic microbes. Currently, our country has not been study yet. Therefore, we carried out research to determine the relationship between Mongolian samples of acne and acne causing their pathogenic microorganisms. We were interested microflora of Mongolian acne patients. We took samples by swab and obtained from 40 acne patients. The acne patients were 25 females and 15 males with teenagers of 57.5% and 25-52 years old of 42.5%. The samples were cultured on modified GAM agar (Nissui, Japan) under anaerobic conditions at 37°C for 96 hr. P. acnes was identified by PCR and the 16s rRNA gene sequences. Also the samples were cultured on Nutrient agar (Biolab, Hungary), Tryptose soy agar (Biolab, Hungary) in aerobic conditions at 37°C for 48 hr. Staphylococcus epidermidis, Staphylococcus aureus, Micrococcus spp, Staphylococcus capitis and Staphylococcus cohnii were identified by API-STAPH-IDENT (Biomerieux, France). We detected demodex mite by microscope. We were found demodex 45% of all patient. All patients had S.epidermidis, P.acnes had 30% of them, S.aureus in 47.5%, Micrococcus, spp in 27.5%, S.Capitis and S.Cohnii each 5%. We compared our research result with Germany, French, Indian and Japanese researcher’s similar studies. Whereas our research results were more than European acne patients such as P.acnes 16 percent and Staphylococcus 64 percent. However Mongolian acne patient’s microorganisms determined more than European acne patients, P.acnes determined 32 percent lower than Japan and Indian patients. Even though Staphylococcus was 47 percent more than their result. Our study shows in causing acne, especially severe acne is associated cases demodex mite, P. Acnes, S.epidermidis. And the strains of bacteria S.aureus, Micrococcus spp conditions from acne were related degree occur in acne but complications. Appearance acne bacteria S. capitis, S.cohnii samples, but only casually. Mongolian people causing acne, pathogenic species had a relatively high percent of people in other countries, S.epidermidis acne compared to the complete condition pathogenic type of acne vulgaris.